2008
DOI: 10.1128/mcb.00596-08
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Replication Checkpoint Directly Regulates MBF-Dependent G1/S Transcription

Abstract: The DNA replication checkpoint transcriptionally upregulates genes that allow cells to adapt to and survive replication stress. Our results show that, in the fission yeast Schizosaccharomyces pombe, the replication checkpoint regulates the entire G 1 /S transcriptional program by directly regulating MBF, the G 1 /S transcription factor. Instead of initiating a checkpoint-specific transcriptional program, the replication checkpoint targets MBF to maintain the normal G 1 /S transcriptional program during replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 35 publications
6
69
0
1
Order By: Relevance
“…4B). This finding could reflect either a defect in cell cycle progression in ⌬tor1 mutants or a more direct defect in activating the transcriptional response to HU (5)(6)(7)46).…”
Section: Tor1mentioning
confidence: 91%
“…4B). This finding could reflect either a defect in cell cycle progression in ⌬tor1 mutants or a more direct defect in activating the transcriptional response to HU (5)(6)(7)46).…”
Section: Tor1mentioning
confidence: 91%
“…We generated different strains that either were expressing chimeras of a fluorescent protein (YFP or GFP) fused to MBF-regulated genes (Cdc22-YFP, Yox1-GFP or Tos4-GFP) or were expressing YFP directly under the control of MBF-regulated promoters (pcdc18, pcdt2, pmik1 or ptos4). 3,11,13,14 By microscopic observation, we could detect fluorescence in each of the 7 strains that we tested, but with different intensity. Since we wanted to establish a method that would allow quantifying this fluorescence, we decided to determine their intrinsic fluorescence on the cytometer.…”
Section: Resultsmentioning
confidence: 99%
“…This result is interesting MBF-dependent gene expression. 3,[20][21][22] Interestingly, one aspect of this regulation involves phosphorylation of the Nrm1 repressor by Cds1 which results in derepression of MBF-dependent gene expression. 13,23 Here, we have further investigated the potential role(s) and regulation of the Yox1 homeodomain transcription factor in S. pombe.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work demonstrated that MBF-regulated gene expression is upregulated in response to activation of the Rad3-dependent DNA replication checkpoint. 3,[20][21][22] Hence, we next examined whether Yox1 plays any role(s) in Rad3 checkpoint-regulated expression of MBF-dependent genes. Cells lacking Rad3 function display increased sensitivity to hydroxyurea (HU) and ultraviolet (UV) light (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation